Technocracy in contemporary scientific, legal, and administrative work - Huaylupo Alcázar, Juan A. (2025)
The essay reflects on the importance assigned to techniques in research work and in everyday social relations, which were structured by the mechanicism of Isaac Newton (1643-1727), principles that were supposed to have the capacity to understandall phenomena, the world and the universe. Far from being forgotten or being part of the history of science, they have been revitalized, not only by George Berkeley (1685-1753), but also by the extraordinary growth and expansion of techniques in the present globalized world, both in the productive, mercantile and financial fields and in all services in society. Likewise, mechanicism is present in the regulations, controls and legal and administrative determinations in social relations, as well as in the establishment of mechanistic patterns in the work of science and research. These tendencies paradoxically predict superiority over their creators and the achievements of humanity. These tendencies paradoxically predict superiority towards their creators and the achievements of humanity.